The Effects of Preeclampsia Severity and Thrombocytopenia on the Prognosis of Hypertensive Pregnant Women - Beşe, Emre; Devran Bıldırcın, Fatma; Malatyalıoğlu, Erdal (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: The present study was aimed to determine the effects of preeclampsia severity and thrombocytopenia on maternal and fetal prognosis in hypertensive pregnant women, and to discuss the clinical and biochemical findings in light of the literature. STUDY DESIGN: Three hundred and one pregnant patients, who had been admitted to the Department of Obstetrics and Gynecology of our clinic, with the diagnosis of preeclampsia between October 2006 and October 2008, were retrospectively evaluated. The patients were divided into two groups as patients with mild and severe preeclampsia. Additionally, the patients were analyzed in two subgroups according to their platelet counts, as the groups with low and normal platelet counts. RESULTS: When the patients with mild and severe preeclampsia were compared with regard to maternal complications, no significant difference was determined between the two groups (p>0.05). However, a significant difference was noted between the groups with respect to the development of eclampsia and HELLP syndrome (p<0.05). Eclampsia (n=17; 12%) and HELLP syndrome (n=30; 21.1%) were more common in the patients with severe preeclampsia. On the other hand, no significant difference was noted between the two groups in terms of fetal outcomes (p>0.05). When the patients with low and the normal platelet counts were compared with respect to maternal complications, it was noted that HELLP syndrome (n=39; 51%) and eclampsia (n=11; 14.5%) were more common in patients with low platelet counts, when compared to the patients with normal platelet counts,and difference between the two groups was significant (p<0.05). Birth weight was significantly lower in patients with low platelet counts (p<0.05). CONCLUSIONS: There is a significant relationship between the severity of preeclampsia and potential complications. The risk for the development of HELLP syndrome and eclampsia increases in patients with severe preeclampsia. Furthermore, the risk for the development of complications increases with a decreased platelet count.